Interior Design Planning of the Indonesian Cultural Center in Berlin, Germany - Santoso, Kezia Viola; Kurniawan, Rizki; Izzati, Alifia Wida (Pendhapa, 2023)
Indonesia is renowned for its rich cultural heritage, yet the global appreciation and understanding of this cultural wealth remain limited. This study addresses the challenge of enhancing international recognition and appreciation of Indonesian culture through the establishment of the Indonesian Cultural Center in Berlin, Germany. The primary objective is to develop an interior design concept that effectively introduces and represents Indonesian culture within a European context. Employing qualitative research methods, including observation, interviews, and surveys, the study focuses on the Embassy of the Republic of Indonesia in Berlin, which serves as the project's location. The research includes comparative analyses of various cultural centers and gathers insights from a diverse group of respondents. Results reveal that a well-curated interior design, incorporating elements such as traditional Indonesian materials, colors, and motifs, can significantly attract and engage German audiences. This study concludes with recommendations for spatial design strategies that balance cultural authenticity with local preferences, aiming to foster greater appreciation of Indonesian culture abroad.